Combined Proteome and Transcriptome Analysis of Heat-Primed Azalea Reveals New Insights Into Plant Heat Acclimation Memory - Wang, Xiuyun; Li, Zheng; Liu, Bing; Zhou, Hong; Elmongy, Mohamed S.; Xia, Yiping (Frontiers in Plant Science, 2020)
Plants can obtain superinduction of defense against unpredictable challenges based on prior acclimation, but the mechanisms involved in the acclimation memory are little known. The objective of this study was to characterize mechanisms of heat acclimation memory in Rhododendron hainanense, a thermotolerant wild species of azalea. Pretreatment of a 2-d recovery (25/18℃, day/night) after heat acclimation (37℃, 1 h) (AR-pt) did not weaken but enhanced acquired thermotolerance in R. hainanense with less damaged phenotype, net photosynthetic rate and membrane stability than nonacclimation pretreated (NA-pt) plants. Combined transcriptome and proteome analysis revealed that a lot of heat-responsive genes still maintained high protein abundance rather than transcript level after the 2-d recovery. Photosynthesis-related genes were highly enriched and most decreased under heat stress (HS) with a less degree in AR-pt plants compared to NA-pt. Sustainably accumulated chloroplast-localized heat shock proteins (HSPs), Rubisco activase 1 (RCA1), beta-subunit of chaperonin-60 (CPN60β) and plastid transcriptionally active chromosome 5 (pTAC5) in the recovery period probably provided equipped protection of AR-pt plants against the subsequent HS, with less damaged photochemical efficiency and chloroplast structure. In addition, significant higher levels of RCA1 transcripts in AR-pt compared to NA-pt plants in early stage of HS showed more important role of RCA1 than other chaperonins in heat acclimation memory. The novel heat-induced RCA1, rather than constitutively expressed RCA2 and RCA3, showed excellent thermostability after 7 d of HS and maintained balanced Rubisco activation state in photosynthetic acclimation. This study provides new insights into plant heat acclimation memory, and indicates candidate genes for genetic modification and molecular breeding in thermotolerance improvement.